Фіскальна ефективність податкової системи у працях закордонних і вітчизняних дослідників - Педько, Андрій Борисович; Маряниченко, Богдан Валерійович (Видавничий дім «Гельветика», Одеса, 2024)
UKR: У статті досліджуються наукові праці, в яких розглядається проблематика зниження фіскальної ефективності сучасної системи оподаткування під впливом глобалізації світової економіки. У попередніх авторських публікаціях були визначені чинники суб’єктивного впливу на процеси формування податкової системи у минулому столітті і сформульована гіпотеза про неминуче зниження фіскальної ефективності податкових систем, побудованих на засадах суб’єктивізму. Тому в даній публікації зосереджено увагу на аналізі наукових праць закордонних і вітчизняних дослідників, що висловлювали й обґрунтовували подібні гіпотези. Було встановлено, що переважна більшість існуючих досліджень лише констатують негативний вплив глобалізації світової економіки на ефективність фіскальних механізмів, але натомість не пропонують конкретних механізмів вирішення цієї проблеми. Де-факто розвинені країни світу вже перебувають на порозі фундаментальної зміни податкової моделі, хоча й дотепер світові експерти не сформулювали чіткої візії податкової реформи, націленої на вирішення проблем, спричинених глобалізацією. Першим кроком до реформування існуючої податкової системи в країнах «Великої сімки» і ОЕСР вважається посилення контролю за прозорістю фінансових транзакцій та інтенсифікація обміну фіскальною інформацією між податковими органами різних країн. Авторське дослідження проводилося із залученням низки загальнонаукових і спеціальних методів.

ENG: The article examines scientific works in which the problem of reducing the fiscal efficiency of the modern taxation system under the influence of the globalization of the world economy is considered. In the author's previous publications, the factors of subjective impact on the processes of formation of the tax system in the last century were determined, and a hypothesis was formulated about the inevitable decrease in the fiscal efficiency of tax systems built on the basis of subjectivism. Therefore, this publication analyzes the scientific works of foreign and domestic researchers who expressed and substantiated similar hypotheses. The article's authors indicate fundamental changes in the world economy that contribute to a decrease in the fiscal efficiency of existing tax systems. Using the example of the movement of tangible and intangible assets between the United States and a country with preferential taxation, the relationship between globalization and the reduction of tax revenues, i.e., the reduction of fiscal efficiency, is illustrated. It was established that the vast majority of existing studies only state the negative impact of the globalization of the world economy on the effectiveness of fiscal mechanisms but instead do not offer specific mechanisms for solving this problem. De facto, the developed countries of the world are already on the threshold of a fundamental change in the tax model, although until now, world experts have not formulated a clear vision of tax reform aimed at solving the problems caused by globalization. The first step towards reforming the existing tax system in the G7 and OECD countries is considered to be strengthening control over the transparency of financial transactions and intensifying the exchange of fiscal information between tax authorities of different countries. The publication indicates two main directions for further transformation of the tax system, which are the focus of attention of modern experts and the scientific community. The author's research was carried out with the involvement of a number of general scientific and special methods.
Fiscal Efficiency of the Tax System in the Works of Foreign and Domestic Researchers
А. Педько: ORCID 0009-0007-9941-0518; Б. Маряниченко: ORCID 0009-0008-0498-906X
Keywords: податкова система; теорії оподаткування; глобалізація економіки; прогресивне оподаткування; пропорційне оподаткування; tax system; theories of taxation; globalization of the economy; progressive taxation; proportional taxation; КЕП (ІПБТ); SOCIAL SCIENCES::Business and economics